Pediatric liver transplantation activity in a high‐volume program during the COVID‐19 pandemic in Brazil. (16th August 2021) - Fonseca, Eduardo A.; Feier, Flavia; Pugliese, Renata; Freitas, Aline F.; Porta, Gilda; Miura, Irene; Baggio, Vera; Kondo, Mario; Benavides, Marcel; Vincenzi, Rodrigo; Roda, Karina; Oliveira, Caio V.; et al.
Abstract: Background: The impact of the COVID pandemic on liver transplant (LT) programs varied among countries. Few data are available about that impact in pediatric liver transplant (PLT) programs. This study aimed at comparing the data of our program in Brazil (2019 vs. 2020). Methods: Retrospective cohort study. Results: One hundred and seventy‐four PLT were performed in the period (93% living donors). Patients were divided into two groups according to the LT date: pre‐COVID‐19 period (march/2019–February/2020) and COVID‐19 period (March/2020–February 2021). In the pre‐COVID‐19 period, 97 LTs were performed, and 77 LTs were performed in the COVID‐19 period. Patients in the COVID‐19 period were younger (10.9 months vs. 16 months, p 0.009), had higher PELD scores (15 vs. 14, p 0.04), more ascites (66.2 vs. 51.5%, p 0.03), and more frequently hospitalized before LT (27.3 vs. 17.5%). However, there was no difference in post‐LT complications, retransplantation nor survival rates. Six (6.2%) patients from pre‐COVID‐19 period were COVID positive at a median of 15.5 months (14–17.5), and 6 (7.8%) patients from COVID‐19 period were COVID positive at a median of 3 months (20 days–6 months) from LT. There was neither mortality nor complications in those patients. Four (33%) were hospitalized, and one had prolonged intubation. Four (33%) were asymptomatic, 4 (33%) had upper airways symptoms, and the remaining had gastrointestinal symptoms. Conclusion: Overall, PLT was not affected during COVID‐19 period. Even though patients from COVID‐19 period were sicker, there was no significant impact in LT outcomes. All the recipients who tested positive for COVID had a favorable outcome.